The Impact of Lean Management on Sustainable Performance: The Moderating Role of Employee Performance in the Steel Industry - Thawornsujaritkul, Thitirat; Boonnual, Chutimant (Journal of Ecohumanism, 2024)
Sustainability has become a global imperative, positioning Lean management as a critical approach to achieving this goal, with employee performance efficiency playing a vital role in industrial manufacturing. Therefore, this study investigates how Lean waste management practices, supported by employee engagement, enhance sustainable performance in the steel industry, aligning with ESG indicators and the Sustainable Development Goals (SDGs). The model is empirically validated using Partial Least Squares Structural Equation Modeling (PLS-SEM) based on 385 responses from executives of steel manufacturing plants in the Eastern Region of Thailand. The findings reveal that lean management practices have a significant positive impact on sustainability, contributing to improved environmental, governance, and social outcomes. Employee performance also directly influences sustainability and has a strong positive effect on waste management, emphasizing its critical role in enhancing operational efficiency and sustainable practices. Interestingly, the study finds that employee performance significantly and negatively moderates the relationship between lean management and sustainability. This indicates that while high-performing employees enhance sustainability through their direct contributions, their overall effectiveness in operational areas may reduce the specific measurable impact of lean practices on sustainability outcomes. The results highlight the importance of integrating employee engagement and lean management strategies to optimize sustainability in the steel industry. Organizations are encouraged to foster a culture of continuous improvement and align operational strategies with human resource capabilities to achieve long-term sustainable success.